2014
DOI: 10.1097/sap.0b013e3182956475
|View full text |Cite
|
Sign up to set email alerts
|

Revision Decompression and Collagen Nerve Wrap for Recurrent and Persistent Compression Neuropathies of the Upper Extremity

Abstract: Here we report on the novel technique of using a collagen matrix wrap in recurrent compression neuropathies with good success. The collagen wrap allows nerve gliding, protection from perineural scar formation, and a favorable microenvironment. Submuscular transposition seems to be no better than other methods of decompression for recurrent cubital tunnel syndrome in contrary to traditional teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 44 publications
1
62
0
1
Order By: Relevance
“…To overcome this problem, collagen materials have recently been developed as an alternative to autologous veins . Vein wrapping was first employed in the upper extremity to avoid scarring in peripheral nerve injury .…”
mentioning
confidence: 99%
“…To overcome this problem, collagen materials have recently been developed as an alternative to autologous veins . Vein wrapping was first employed in the upper extremity to avoid scarring in peripheral nerve injury .…”
mentioning
confidence: 99%
“…Collagen has both supportive animal and human data. 69 Porcine SIS (AxoGen, Inc., Alachua, FL) prevented adhesion formation around rabbit sciatic nerves at 1, 2, and 6 mo after implantation. Kim et al 68 demonstrated decreased connective tissue formation at the repair site, but no other significant difference between wrapped and nonwrapped rodent nerve repairs.…”
Section: Off-the-shelf Optionsmentioning
confidence: 99%
“…[30,76] Reisman and Dellon [58] Abductor digiti minimi Median Pain reduction in 11/12 patients (91) Strickland et al [59] Hypothenar fat pad flap Median Excellent results in alleviating recalcitrant idiopathic CTS (95 satisfaction in 62 patients) Rose [60] Palmaris brevis muscle flap Median Complete pain relief in all patients (13 hands) (100) Jones [61] Pedicled or free flaps Median/ulnar Pain reduction in 7/9 patients (78) Giunta et al [62] Hypothenar fat pad flap Median Pain reduction in 8/9 patients (89) Frank et al [63] Hypothenar fat pad flap Median Pain reduction in 8/9 patients (89) Guillemot et al [64] Fat graft Median No pain reduction in 4 patients Mathoulin et al [65] Hypothenar fat pad flap Median Pain resolution in 41/45 patients (98) De Smet and Vandeputte [66] Hypothenar/ulnar fat pad flap Median Pain reduction in 9/14 patients (64) Dahlin et al [67] Pedicled ulnar, dorsal forearm flaps Free groin, scapular, lateral arm flaps Median Pain reduction in 10/14 patients (71) Goitz and Steichen [54] Free omental flaps Median Pain reduction in 7/11 patients (63) Luchetti et al [68] Fascial and fasciocutaneous island flaps (hypothenar fat pad, forearm radial artery, forearm ulnar artery, ulnar fascial fat, and posterior interosseous) Median Four point VAS score reduction in 23/25 patients (92) Craft et al [69] Hypothenar fat pad flap Median Pain resolution in 83% of 28 patients Fusetti et al [70] Hypothenar fat pad flap Median Pain reduction in 18/20 patients (90) Elliot et al [71] Vascularized forearm fascial flap Median/ulnar Pain resolution in 8/14 patients (57) Soltani et al [43] Collagen: neurolysis + collagen wrap Median/ulnar Resolution/improvement in 4 patients (median) Resolution in 3/4 patients (cubital tunnel syndrome) Espinoza et al [72] Microneurolysis alone versus ADCON/TN Median/ulnar Pain reduction in 80% of 54 patients Atzei et al [35] Neurolysis or nerve repair with Hyaloglide (R) Hand nerves Pain reduction quicker with Hyaloglide (R) 14 patients treated with HA versus 16 treated without gel Varitimidis et al [73] Autologous vein Median Pain reduction in 14/15 patients (93) Masear [74] Vein: autologous+allograft Median and various peripheral nerves…”
Section: Scar Neuritis and Outcomes: Literature Reviewmentioning
confidence: 99%
“…Its effectiveness is similar to that of other anti-adhesion devices, but it entails a lower fewer risk of complications compared to wrapping the nerve in autologous tissue such as vein (Neura Wrap; Integra LifeSciences, Plainsboro, NJ, USA). [43] There are therefore several different types of anti-adhesion devices, but scant information as to which is the most effective at the clinical and preclinical level, even though all seem to limit perineural scarring formation without any particular side effects. A major advantage is their fast application and less invasive surgical dissection, without the need for further procedures (and possible attendant injury), which considerably reduces operating time compared to the surgical approaches described above.…”
Section: Surgical Management After Neurolysis Commercial Gels and Antmentioning
confidence: 99%
See 1 more Smart Citation